2014
DOI: 10.30638/eemj.2014.250
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Assessing Danube Delta Systems With Macro Invertebrates

Abstract: This study, analyzes the benthic macroinvertebrates community structure and composition in order to assess the ecological status as required by the Water Framework Directive (WFD). Macroinvertebrates are the appropriate indicators to describe habitat heterogenity and the water bodies ecological status by turning the allochtone material into biomass, which is then transferred to the upper trophic levels. Moreover, the macroinvertebrates have the capacity to integrate in their structure the effects of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Our seasonal monitoring studies during the period 2003-2013 in the Danube Delta -Sfantu-Gheorghe Branch revealed higher metal concentrations (Hg, Cu, Ni, Cd, Cr, Pb, Hg, As) in the sediment than water, due to sediment storage capacity, but all together their concentrations were within the admissible limits. Moreover, metals Cu, Pb, Zn, Cr, Ni, Cd, Mn and Fe were the most abundant in sediments from Danube Delta [9][10][11]. This data has been used as a basic criterion of the metal selection [12][13][14].…”
mentioning
confidence: 99%
“…Our seasonal monitoring studies during the period 2003-2013 in the Danube Delta -Sfantu-Gheorghe Branch revealed higher metal concentrations (Hg, Cu, Ni, Cd, Cr, Pb, Hg, As) in the sediment than water, due to sediment storage capacity, but all together their concentrations were within the admissible limits. Moreover, metals Cu, Pb, Zn, Cr, Ni, Cd, Mn and Fe were the most abundant in sediments from Danube Delta [9][10][11]. This data has been used as a basic criterion of the metal selection [12][13][14].…”
mentioning
confidence: 99%
“…Secondly, the tailing pond having the GPC coordinates Lat: 45°57'38.97"N, Long: 22°58'55.39"E is situated on Valea Mealului, tributar y to the Cartej river, about 3 km downstream of the Certej preparation plant, near Certejul de Sus, in the south of the Metaliferi Mountains. This tailing pond has a total surface area of 42,33ha, a canopy of 59 meters and a volume of 5,8 mil m 3 (fig. 1).…”
Section: Sampling Of Waste Waters and Sediment Samplesmentioning
confidence: 99%
“…In recent years, various chemical compounds such as organic and inorganic micropollutants have been detected in high concentrations in waste water, including hazardous metals with a high toxic effect to human health and the environment [1][2][3]. It has been known that the hazardous metals in low concentrations were toxic and had a tendency to bio accumulate both in the environment and in the human body, affecting functions of the central nervous system, blood composition, liver, kidney of the lungs and it could ultimately cause death [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…Population growth, industrialization and urbanization have generated an increase in wastewater flows and the more stringent environmental regulations led to the need for innovative treatment technologies, with high efficiencies and reduced operational costs [1,2]. Mathematical models implementation is needed both in the design phase and in the optimizing stage of wastewater treatment plants (WWTPs) [3].…”
mentioning
confidence: 99%